L’Indépendance du Venezuela : idéalisation de l’histoire et paradigme du héros - Frédérique Langue (Caravelle)
This essays aims to analyze the use of bolivarian myths in Venezuelan history from point of view of the history of ideas and representations. So its focuses on long term interpretation in order to emphasize the political imaginary of Bolivarian Republic. It points out to the fact that, along with Independence consecrated chronology and homeland centered historiography, come up matters and passions frequently forgotten by academic history but recovered by the new official history.